Integrasi Nilai Islam dan Total Quality Management: Model Pendekatan Mutu Berbasis Spiritualitas untuk Optimalisasi Pendidikan Islam - Ummul Khoiroh; Misbahul Arifin; Dian Zulfatul Iman (Education Research Center, 2025)
This study focuses on integrating Islamic values with the concept of Total Quality Management (TQM) as a holistic approach to enhancing the quality of Islamic education. The main objective is to formulate a spiritually based quality approach model that harmonizes modern management principles with Islamic values to support the sustainable optimization of Islamic educational institutions. This research employs a qualitative approach with a field study design conducted at MA Nurul Jadid Paiton, Probolinggo Regency, alongside library research with a descriptive-analytical method. Data were collected through participatory observation, in-depth interviews with school leaders and teachers, and documentation. The findings reveal that integrating Islamic values, such as sincerity (ikhlas), trustworthiness (amanah), excellence (ihsan), and deliberation (musyawarah) into TQM principles, including customer focus (student-centeredness), continuous improvement, and total involvement, significantly contributes to establishing a culture of quality that is not only rational and systematic but also spiritual and transcendental. The implication of this model is the development of a more meaningful, sustainable, and spiritually grounded management system in Islamic education, capable of responding to modern challenges without abandoning its religious foundation.